Kompetensi Profesional Guru sebagai Penunjang Prestasi Siswa: Studi Kasus di SMPIT Ruhama Tangerang Selatan - Suprianto, Ahmad (Prodi Pendidikan Agama Islam IAINU Kebumen, 2023)
This article aims to elaborate on the extent of the teacher's professional role in shaping student success towards achievement. The research objects in this research are class VIII students of SMPIT Ruhama South Tangerang in the field of Islamic Religious Education (PAI) subjects. This research uses the library research method with a descriptive analytical approach. Class VIII students as the main data were then carried out in-depth analysis of the data obtained through observation and interviews and compared with data related to the results of previous research. This article concludes that professional teachers have an important role in delivering achieving students, it's just that these professionals need media tools to support teaching.